Design like you give a damn. [2], Building change from the ground up - Aaronson, Deborah; Architecture for Humanity (Organization) (New York ; London : Abrams, 2012)
With the rise in social demand for recycling programs and sustainable living, this volume documents more than 100 new projects from around the world. It is packed with practical and ingenious design solutions that address the need for basic shelter, housing, education, health care, clean water and renewable energy.
Disaster reconstruction -- Introduction architecture for humanity: lessons learned -- Financing sustainable community development -- Bamboo shelter -- Soe Ker Tie Hias (butterfly houses) -- Transitional to what? -- Katrina cottage -- Ma'erkang steel frame housing -- LIFT house -- Alluvial sponge comb -- Make it right -- Biloxi model home program -- DeLisle community center -- Rector Street bridge -- what if New York City... Housing -- Overview of green rating systems -- enviRenew -- New house project -- Tour Bois-le-Pretre -- Lift in 1.5 x 30 -- Venezuelan eco-cabanas -- 100K house -- Superuse harvest map -- Diez Casas para Diez familias (10x10) -- 10x10 housing initiative -- Tassafaronga village -- Solar decathlon -- Galisteo basin preserve -- Western harbour B001 development -- Community -- Gathering spaces -- Marsupial bridge & media garden -- Tiuna el Fuerte cultural park -- High line -- Centre pour le Bien-être des Femmes (CBF) -- SOS children's villages Lavezzorio community center -- Education -- Fuji kindergarten -- Green school Bali -- Olifantsvlei primary school -- Bridge school -- Hazelwood school for children and young people with sensory impairment -- Health -- Maggie's cancer caring centres -- Friends center at Angkor hospital for children -- Pebble project -- Sports for social change -- Mahiga Hop high school Rainwater Court -- Skateistan -- Gimnasio vertical -- Sacred spaces & memorials -- Chapel of San Isidro Labrador -- La Ruta del Peregrino -- Anti-memorial to heroin overdose victims -- Estadio nacional, memoria nacional -- Basic services & materials -- Emergency water bladder -- Rainwater HOG -- Sundolier -- Ceramic pillars -- Ecological concrete additives -- Papercrete -- Plastiki rPET -- Politics, policy & planning -- Arts & culture -- Favela painting project -- Faces of favelas -- L.A.S.E.R. tag -- Cool biz -- Greywater action -- Community development -- In-situ slum rehabilitation -- Brick city: Mayor Cory Booker -- Transition network -- Green light for midtown -- Waling school bus -- Crowd-sourced planning -- Let's do it! -- Light pollution -- Crowd-sourced mapping -- Access to food -- Food deserts -- Smarter lunchrooms -- Svalbard global seed vault -- Peace & security -- Violence prevention through urban upgrading -- Red hook community justice center -- Trau Kod Dam -- Proyecto urbano integral.
Includes bibliographical references (p. 326-328).
Keywords: Sustainable architecture; Architecture and society; Sustainable urban development; Sustainable buildings -- Design and construction; Emergency housing -- Design and construction; Buildings, Temporary -- Design and construction